Racial differences in coronary artery calcification in older adults. - Newman, Anne B; Naydeck, Barbara L; Whittle, Jeff; Sutton-Tyrrell, Kim; Edmundowicz, Daniel; Kuller, Lewis H (Arterioscler Thromb Vasc Biol, 2002)
Reports on race-related differences in coronary artery calcium (CAC) are just beginning to emerge and have not been well studied in the elderly. This study was undertaken to assess whether such differences exist and the relationship between CAC and cardiovascular risk factors in a cohort of elderly community-dwelling adults. CAC was measured by using electron-beam tomography in 614 adults (aged 67 to 99 years), of whom 59% were women and 23% were black. The median CAC score was lower in blacks than in whites for men (159 versus 787, respectively; P<0.001) and for women (134 versus 233, respectively; P=0.02) after adjustment for age, cardiovascular disease, and risk factors for cardiovascular disease, although this difference was stronger and remained significant among men only. Lower CAC scores were also observed in the subgroup of blacks with a history of myocardial infarction. The lower CAC scores in blacks compared with whites observed in this study is consistent with either a lower prevalence of coronary artery disease or a lower extent of calcification of coronary artery disease.
Keywords: Age Factors; Aged; Calcinosis; Cohort Studies; Coronary Artery Disease; Female; Humans; Logistic Models; Male; Risk Factors; Sex Factors; Tomography, X-Ray Computed

Relationship between coronary artery calcification and other measures of subclinical cardiovascular disease in older adults. - Newman, Anne B; Naydeck, Barbara L; Sutton-Tyrrell, Kim; Edmundowicz, Daniel; O'Leary, Daniel; Kronmal, Richard; Burke, Gregory L; Kuller, Lewis H (Arterioscler Thromb Vasc Biol, 2002)
BACKGROUND: In the Cardiovascular Health Study, subclinical cardiovascular disease (CVD) predicted CVD events in older adults. The extent to which this measure or its components reflect calcified coronary disease is unknown. METHODS AND RESULTS: Coronary artery calcium (CAC) was assessed with electron beam tomography in 414 participants without clinical CVD and examined using cut points (CAC> or =400 and CAC> or =800) and the log(CAC); 274 had subclinical CVD by ankle-arm index, ECG, or carotid ultrasound. Cut points for subclinical disease as previously defined in the Cardiovascular Health Study were examined as well as continuous measures to produce receiver operating characteristic curve curves. A low ankle-arm index was highly specific for a high CAC score. The internal carotid artery intima-media thickness was most strongly correlated with CAC (r=0.30) and was significantly related to both CAC cut points and to the log(CAC) score independently of all other measures. CONCLUSIONS: In these community-dwelling older adults without clinical CVD, internal carotid artery intima-media thickness was most closely related to CAC. However, 17.5% of those with a CAC> or =400 would be missed in the ascertainment of subclinical atherosclerosis using the previously published composite of subclinical atherosclerosis. Prospective follow-up will determine whether the CAC score improves prediction of CVD events over other noninvasive measures.
Keywords: Aged; Aged, 80 and over; Calcinosis; Cardiovascular Diseases; Carotid Stenosis; Cohort Studies; Coronary Artery Disease; Demography; Female; Humans; Male; Prevalence; Risk Factors; Sensitivity and Specificity; Sex Factors; Tomography, X-Ray Computed; Tunica Intima; Tunica Media

"Successful aging": effect of subclinical cardiovascular disease. - Newman, Anne B; Arnold, Alice M; Naydeck, Barbara L; Fried, Linda P; Burke, Gregory L; Enright, Paul; Gottdiener, John; Hirsch, Calvin; O'Leary, Daniel; Tracy, Russell (Arch Intern Med, 2003)
BACKGROUND: Cardiovascular diseases are the primary cause of death in older adults. Among those without clinical disease, high levels of subclinical disease are associated with poor survival. The effect of the extent of subclinical cardiovascular disease on the quality of the remaining years has not been defined. METHODS: In a longitudinal cohort study, 2932 men and women aged 65 years and older were followed up for 8 years to determine the likelihood of maintaining intact health and functioning. Successful aging was defined as remaining free of cardiovascular disease, cancer, and chronic obstructive pulmonary disease and with intact physical and cognitive functioning. RESULTS: Younger age at study entry and a lower extent of subclinical cardiovascular disease were independently associated with the likelihood of maintaining successful aging. In age-stratified summaries, those with subclinical disease had a trajectory of decline similar to subjects 5 years older without subclinical vascular disease. Regression analyses showed that the decline associated with subclinical disease was equivalent to 6.5 (95% confidence interval, 6.4-6.6) years of aging for women and 5.6 (95% confidence interval, 5.4-5.8) years of aging for men. Individual measures of the extent of cardiovascular disease, diabetes mellitus, smoking, and higher C-reactive protein level were also independently predictive of fewer years of successful aging, but none of these factors substantially attenuated the effect of age itself. CONCLUSIONS: There is a graded relationship between the extent of vascular disease measured noninvasively and the likelihood of maintaining intact health and function. Prevention of subclinical vascular disease may increase the quality and the quantity of years in late life.
Keywords: Aged; Aged, 80 and over; Aging; C-Reactive Protein; Cardiovascular Diseases; Female; Health Status; Humans; Longitudinal Studies; Male; Quality of Life; Regression Analysis; Risk Factors

Coronary artery calcium and physical function in older adults: the Cardiovascular Health Study. - Inzitari, Marco; Naydeck, Barbara L; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2008)
BACKGROUND: In older adults without clinical cardiovascular disease, coronary artery calcium (CAC) is associated with other subclinical vascular diseases, which, in turn, predict physical dysfunction. However, the association between CAC and physical function is unstudied. METHODS: In 387 older community-dwellers from the Cardiovascular Health Study without clinical cardiovascular diseases (mean age +/- standard deviation = 78.7 +/- 3.7, 35% men, 22% African Americans), CAC was measured using electron beam tomography, and physical performance was assessed by usual pace gait speed, chair stand, and tandem stand. Differences in physical performance across CAC quartiles were investigated in the whole cohort and by gender. Associations with gait speed (m/s) were assessed in multivariable models using both the continuous form of CAC score (log(CAC)) and quartiles of CAC, adjusting for demographics and comorbidities. RESULTS: No differences in physical performance were observed across CAC quartiles in the whole group. In gender-stratified analyses, a significant association was shown among women, who had progressively lower gait speed across CAC quartiles: Those with CAC > 220 walked more than 0.1 m/s slower than those with CAC < 35 (age-adjusted ptrend =.017). After multivariable adjustment, the association remained statistically significant for women in both linear (log(CAC) and gait speed, p =.025) and logistic models: Each of the top three CAC quartiles (35-220, 221-659, and > or = 660) had a more than twofold odds of walking slower than 1 m/s, compared to the lowest CAC quartile (< 35; p =.021). CONCLUSIONS: In this sample of older community-dwellers without overt cardiovascular disease, CAC was inversely related to gait speed in women, but not in men.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Calcinosis; Coronary Artery Disease; Female; Geriatric Assessment; Humans; Male; Regression Analysis; Risk Factors; Tomography, X-Ray Computed; Walking

Coronary artery calcium, carotid artery wall thickness, and cardiovascular disease outcomes in adults 70 to 99 years old. - Newman, Anne B; Naydeck, Barbara L; Ives, Diane G; Boudreau, Robert M; Sutton-Tyrrell, Kim; O'Leary, Daniel H; Kuller, Lewis H (Am J Cardiol, 2008)
Few population studies have evaluated the associations of both coronary artery calcium (CAC) and carotid ultrasound with cardiovascular events, especially in adults >70 years of age. At the Pittsburgh Field Center of the Cardiovascular Health Study, 559 men and women, mean age 80.2 (SD 4.1) years had CAC score assessed by electron beam computerized tomographic scan and common and internal carotid artery intimal medial wall thickness (CCA-IMT and ICA-IMT) by carotid ultrasound between 1998 and 2000 and were followed for total and incident cardiovascular disease events through June 2003. Crude rates and hazard ratios for total and incident events were examined with and without adjustment for cardiovascular risk factors. After 5 years, there were 127 cardiovascular disease events, 48 myocardial infarctions or cardiovascular disease deaths, and 28 strokes or stroke deaths. Total and incident cardiovascular disease event rates were higher in each quartile of CAC and CCA-IMT, but not of ICA-IMT. For total cardiovascular disease, the adjusted hazard ratio for the fourth versus first quartile of CAC was 2.1 (95% confidence interval 1.2 to 3.9) and for CCA-IMT was 2.3 (95% confidence interval 1.3 to 4.1). The CCA-IMT was more strongly related to stroke risk than was CAC, although CAC was also an important predictor of stroke. No significant gender differences were found, although relative risks appeared to be stronger in women, especially for stroke. In conclusion, in adults >70 years of age, CAC and CCA-IMT had similar hazard ratios for total cardiovascular disease and coronary heart disease. The CCA-IMT was more strongly related to stroke than CAC, but CAC was also a predictor of stroke.
Keywords: Aged; Aged, 80 and over; Carotid Artery Diseases; Carotid Artery, Common; Carotid Artery, Internal; Coronary Artery Disease; Coronary Vessels; Female; Humans; Male; ROC Curve; Severity of Illness Index; Survival Analysis; Ultrasonography; United States

Incident physical disability in people with lower extremity peripheral arterial disease: the role of cardiovascular disease. - Brach, Jennifer S; Solomon, Cam; Naydeck, Barbara L; Sutton-Tyrrell, Kim; Enright, Paul L; Jenny, Nancy Swords; Chaves, Paulo M; Newman, Anne B (J Am Geriatr Soc, 2008)
OBJECTIVES: To evaluate the risk of incident physical disability and the decline in gait speed over a 6-year follow-up associated with a low ankle-arm index (AAI) in older adults. DESIGN: Observational cohort study. SETTING: Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Allegheny County, Pennsylvania. PARTICIPANTS: Four thousand seven hundred five older adults, 58% women and 17.6% black, participating in the Cardiovascular Health Study. MEASUREMENTS: AAI was measured in 1992/93 (baseline). Self-reported mobility, activity of daily living (ADL), and instrumental activity of daily living (IADL) disability and gait speed were recorded at baseline and at 1-year intervals over 6 years of follow-up. Mobility disability was defined as any difficulty walking half a mile and ADL and IADL disability was defined as any difficulty with 11 specific ADL and IADL tasks. Individuals with mobility, ADL, or IADL disability at baseline were excluded from the respective incident disability analyses. RESULTS: Lower baseline AAI values were associated with increased risk of mobility disability and ADL/IADL disability. Clinical cardiovascular disease (CVD), diabetes mellitus, and interim CVD events partially explained these associations for mobility disability and clinical CVD and diabetes mellitus partially explained these associations for ADL and IADL disability. Individuals with an AAI less than 0.9 had on average a mean decrease in gait speed of 0.02 m/s per year, or a decline of 0.12 m/s over the 6-year follow-up. Prevalent CVD partly explained this decrease but interim CVD events did not further attenuate it. CONCLUSION: Low AAI serves as marker of future disability risk. Reduction of disability risk in patients with a low AAI should consider cardiovascular comorbidity and the prevention of additional disabling CVD events.
Keywords: Activities of Daily Living; Aged; Cardiovascular Diseases; Cohort Studies; Comorbidity; Disability Evaluation; Female; Gait; Geriatric Assessment; Humans; Lower Extremity; Male; Mobility Limitation; Peripheral Vascular Diseases; Proportional Hazards Models; Risk Assessment; Risk Factors; United States

A physiologic index of comorbidity: relationship to mortality and disability. - Newman, Anne B; Boudreau, Robert M; Naydeck, Barbara L; Fried, Linda F; Harris, Tamara B (J Gerontol A Biol Sci Med Sci, 2008)
BACKGROUND: In older adults, there is often substantial undiagnosed chronic disease detectable on noninvasive testing, not accounted for by most comorbidity indices. We developed a simple physiologic index of comorbidity by scoring five noninvasive tests across the full range of values. We examined the predictive validity of this index for mortality and disability. METHODS: There were 2928 (mean age 74.5 years, 60% women, 85% white, and 15% black) participants in the Cardiovascular Health Study (1992-1993) who had carotid ultrasound, pulmonary function testing, brain magnetic resonance scan, serum cystatin-C, and fasting glucose. These were combined into a single physiologic index of comorbid chronic disease on a scale of 0-10. Cox proportional hazard models were used to predict mortality, mobility limitation, and activities of daily living (ADL) difficulty after a maximum of 9 years. RESULTS: The range of the physiologic index was quite broad, with very few individuals having total scores of either 0 or 10. Those with an index of 7-10 had a hazard ratio of 3.80 (95% confidence interval, 2.82-5.13) for mortality compared to those with scores of 0-2, after adjustment for demographics, behavioral risk factors, and clinically diagnosed conditions. Associations with mobility limitation and ADL difficulty were also significant. The index explained about 40% of the age effect on mortality risk. CONCLUSION: Older adults with low levels of markers of chronic disease are rather rare but have remarkably good health outcomes. The ability of such an index to distinguish usual from low risk might provide an opportunity to better understand optimal health in old age.
Keywords: Activities of Daily Living; Aged; Comorbidity; Disabled Persons; Female; Health Status; Humans; Male; Mobility Limitation; Mortality; Predictive Value of Tests; Proportional Hazards Models